Urinary tract infections in a Pediatric Emergency Department – Etiology and antibiotic susceptibility patterns - Santos, Paula; Nascimento, Ana Sofia; Santos, Filomena; Ribeiro, Catarina; Morais, Julieta (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Introduction: Urinary tract infections are common in children. The decision to start empiric antibiotic therapy before isolation of the causative agent must be made based on the clinical presentation and antimicrobial resistance profile of each population. The aim of the present study was to identify the most common etiological agents in urinary tract infections in children and adolescents attending the Pediatric Emergency Department of a level II hospital and the antimicrobial susceptibility pattern, in order to optimize the use of empiric and prophylactic therapy. Material and Methods: A retrospective analysis of urine cultures with a positive result between January 2019 and December 2021 was performed. Results: A total of 774 urine cultures were evaluated. The most frequently isolated etiological agents were Escherichia coli (68.5%), Proteus mirabilis (18.1%), and Staphylococcus saprophyticus (4.7%). Escherichia coli showed 4.9% resistance to cefuroxime and 26.2% resistance to amoxicillin-clavulanic acid. Proteus mirabilis showed an adequate susceptibility profile to all empirically used antibiotics. In adolescents, 26.8% of urinary tract infections were caused by Staphylococcus saprophyticus. Ten cases (1.3%) of extended-spectrum beta-lactamase-producing Enterobacteriaceae were identified. Discussion: Cefuroxime showed an adequate susceptibility profile for all microorganisms. Escherichia coli showed a high resistance rate to amoxicillin-clavulanic acid, exceeding the acceptable resistance threshold for empirical antibiotic therapy. The results suggest an increase in the incidence of urinary tract infections caused by Staphylococcus saprophyticus, which means that the prescription of fosfomycin as first-line empirical therapy for female adolescents should be discouraged.